Patterns of Coaching Student Discipline Through Management Islamic Boarding School in Gontor 2nd Campus at Ponorogo - Abu Darda; Taufik Riski Sista; Fathimah Kamilatun Nisa; Sintya Kartika Prameswari (Jurnal Pendidikan Islam Indonesia, 2023)
Abstract: Islamic Boarding School is a quality educational of institution, at the forefront of fostering human morality. The purpose of this study is to (1) Knowing the application of Islamic Boarding School management in the development of student discipline. (2) Determine the Support and Obstacles to the Factors for the Implementation of Islamic Boarding School Management in a cultivation of student discipline. The research method used by the researcher is a qualitative research method with a phenomenological approach where the discipline enforcement system is a unique phenomenon raised in this study. The data analysis techniques used are Milles and Huberman triangulation form of data reduction, data display, and data verification. The results of this study are (1) The Through manajement of Islamic Boarding School by the implimenting System of POACE (Planning, Organizing, Actuating, Controlling, dan Evaluating) In the Life of Islamic Boarding School. (2) There are supporting and inhibiting factors in the implementation Islamic Boarding School of management at Gontor 2nd Campus.